When Narcissus Became a CEO: CEO Narcissism and Its Effect on Earnings Management - Christian, Patricia Gabriela; Sulistiawan, Dedhy (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study examines the role of CEO narcissism to earnings management. Samples are non-financial companies listed in Indonesian Stock Exchange. Three indicators are used to reflect the CEO's narcissistic nature: CEO photograph, CEO publicity, and CEO's social media. Overall, the principal component analysis of the narcissism variable is not able to explain earnings management. After splitting the indicators, the results show empirical evidence that CEO publicity affects earnings management. This study also documented that CEO publicity stimulates earnings management for firms with more profitability. These findings contribute to earnings management literature by providing evidence that profitability positively affects earnings management, especially for firms with higher CEO narcissism measured by CEO publicity.